A book of bees : --and how to keep them - Hubbell, Sue. (Boston : Houghton Mifflin, 1998)
Chronicles the bee keeper's and the bee's year, beginning in autumn and concluding with summer harvest.
"A Mariner book.".
Includes index.
Originally published: New York : Random House, c1988.
Booklist.
Publisher's Weekly.
Wilson's Public Library.
Keywords: Bee culture; Honeybee; Beekeeping; Bees